2023
DOI: 10.1039/d3cp01746j
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of resonant core-hole spectroscopies of gas-phase free-base phthalocyanine

Abstract: We studied N $1s^{-1}$ inner-shell processes of the free base Phthalocyanine molecule, H$_2$Pc, in the gas-phase. This complex organic molecule contains three different nitrogen sites defined by their covalent bonds....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 71 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…This is not guaranteed by density functional theory based methods that optimize the cation wave functions with an overlap criterion. 11 Figure 2a shows that the theory correctly identifies peaks E, D, and C as the major contributions and correctly describes the relative shape across the spectrum. This result suggests that the ezDyson method is a promising approach for the challenging simulation of mid-sized (>10 atoms) polyatomic molecular photoelectron spectra, with few examples in the literature.…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…This is not guaranteed by density functional theory based methods that optimize the cation wave functions with an overlap criterion. 11 Figure 2a shows that the theory correctly identifies peaks E, D, and C as the major contributions and correctly describes the relative shape across the spectrum. This result suggests that the ezDyson method is a promising approach for the challenging simulation of mid-sized (>10 atoms) polyatomic molecular photoelectron spectra, with few examples in the literature.…”
mentioning
confidence: 80%
“…Several studies have explored the site selectivity in the resonant AM decay following core excitation, based on factors such as the chemical environment, the energy of the excited state, or its symmetry, benchmarked by the experiments outlined in refs . A recent study on HNCO by Holzmeier et al found only minor differences in resonant AM spectra for excitation at C, N, or O sites, or for different intermediate states, while de Moura et al found that excitation at different nitrogen sites in phthalocyanine leads to visible changes in the spectra . These examples highlight the complexity of resonant photoemission and that there are often subtle factors which determine the probability for populating final valence states even when site selectivity is possible.…”
mentioning
confidence: 99%
See 3 more Smart Citations